2020
DOI: 10.1007/s13201-020-01208-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical assessment of groundwater quality for few habitations of Chandel District, Manipur (India)

Abstract: A preliminary hydrogeochemical investigation of groundwater quality for spatially distributed habitations of Chandel district of Manipur was carried out with an objective to assess the suitability of groundwater for different anthropogenic uses. Altogether, eighteen (18) physico-chemical parameters including in situ parameters and major ions were analysed for classification and hydrogeochemical characterisation of groundwater resources of the study area. Some of the anions such as Cl− and SO42− were found in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The average concentration was 380 μs/cm. A relatively higher EC during pre-monsoon may be due to low water availability, higher evaporation rate during this period (Gupta et al 2021;Mayanglambam & Neelam 2022) or dissolution of ions due to weathering of rocks (Alam et al 2020). Gupta et al (2021), also reported higher EC during pre-monsoon period at Kabar Taal, wetland, Bihar that has been linked to higher temperature and evaporation.…”
Section: Hydro Geochemistry Of Ka Wetlandmentioning
confidence: 96%
“…The average concentration was 380 μs/cm. A relatively higher EC during pre-monsoon may be due to low water availability, higher evaporation rate during this period (Gupta et al 2021;Mayanglambam & Neelam 2022) or dissolution of ions due to weathering of rocks (Alam et al 2020). Gupta et al (2021), also reported higher EC during pre-monsoon period at Kabar Taal, wetland, Bihar that has been linked to higher temperature and evaporation.…”
Section: Hydro Geochemistry Of Ka Wetlandmentioning
confidence: 96%
“…There are different colour codes in GIS mapping for showing the distribution of various chemical constituents according to the permissible range as per IS Drinking Water Specifications (IS 10500:1991). Table 2 shows the different colour codes used in GIS mapping for the current study [10].…”
Section: Methodsmentioning
confidence: 99%
“…The groundwater sampled during the pre-monsoon season of 2015 from forty-nine selected wells distributed across 177 the province was evaluated. The data domain selection was in line with the approach adopted by previous 178 researchers such as Singha and Pasupuleti (2020) and Alam et al (2020) Water quality index (WQI)…”
Section: Sampling and Analysis 176mentioning
confidence: 99%